2001
DOI: 10.1046/j.1523-5408.2001.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Cognitive Function

Abstract: Cognitive impairment is a major problem in elderly persons. The possible role of nutrition in the development of cognitive disorders and dementia is a current theme of investigation. This paper discusses a number of possible associations between nutrition and cognitive function, especially hypotheses concerning deficiencies of B vitamins and homocysteine and damage caused by free radicals, along with the potential role of antioxidants in preventing such damage. We present putative mechanisms through which diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Risk factors for dementia include the presence of the apoE4 protein,3 high blood pressure,46 diabetes,7 lipid abnormality,8 depression,9 inactivity,10 low income,11,12 and a decrease in the frequency of interpersonal exchanges 13. Conversely, protective factors include the presence of higher education,14 physical activity,15 participation in cognitive activities,15 antioxidant food intake,16,17 moderate alcohol consumption,18 and increased frequency of social participation and interpersonal exchanges 19. Since effective drugs for this disease have not yet been developed, it is important to reduce the number of risk factors through lifestyle modifications to include as many protective factors as possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for dementia include the presence of the apoE4 protein,3 high blood pressure,46 diabetes,7 lipid abnormality,8 depression,9 inactivity,10 low income,11,12 and a decrease in the frequency of interpersonal exchanges 13. Conversely, protective factors include the presence of higher education,14 physical activity,15 participation in cognitive activities,15 antioxidant food intake,16,17 moderate alcohol consumption,18 and increased frequency of social participation and interpersonal exchanges 19. Since effective drugs for this disease have not yet been developed, it is important to reduce the number of risk factors through lifestyle modifications to include as many protective factors as possible.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of nutrition, recent studies have demonstrated the properties of certain food components that might potentially prevent cognitive impairment and dementia 17. Among them, we focused on soy peptide, which is obtained by hydrolyzing soy protein isolate (SPI) with food processing enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the present study is the first to provide a comprehensive estimate of saccharide intake in adults. Middle-aged individuals were chosen because the first signs of age-associated cognitive decline often become apparent in mid-life ( 31 , 32 ) .…”
mentioning
confidence: 99%
“…Recent research suggests that when conducting investigations into nutrient effects on cognition, it is important to study these effects in middle-age when the first signs of age-associated decline appear and before cognitive difficulties become apparent (Nicolas et al 2001;McDaniel et al 2002). Thus, the current study investigated dietary intake of saccharides, sourced from certain fruits and vegetables, and its relationship to cognitive performance in a group of middle-aged adults.…”
mentioning
confidence: 99%